Proceedings of the 8th Economics &Amp; Finance Conference, London 2017
DOI: 10.20472/efc.2017.008.010
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Relationship Between the Sovereign Credit Default Swaps and the Stock Market of Pakistan Through Handling Outliers

Abstract: This study examines the relationship between the Sovereign Credit Default Swap (SCDS) market and Karachi Stock Exchange (KSE). Previous literature in this lieu rarely handles the effect of outliers' presence in data. This study applies Split Sample Skewness Based Boxplot (SSSBB) technique for outlier detection and proposes SSSBB-Winsorization for handling outliers. The results depict a significant role of outliers in the determination of the correlation and causal relationship between these markets. Findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Considering the CDS–stock connection concentrated on sovereign CDSs, a few studies have examined the relationship between CDS spreads and the stock market at the country level ([ 4 , 20 , 21 , 22 , 23 , 24 ]). Estimating a vector autoregressive generalized conditional heteroskedastic VAR-BEKK(Baba, Engle, Kraft and Kroner) model, with the purpose of explaining the dependency structures between credit spreads and equity returns of the European market (based on iTraxx Europe index, the Dow Jones Euro Stoxx 50 index and the Dow Jones VStoxx index), Schreiber et al [ 20 ] found that the negative relationship between asset prices and credit spreads is valid only for the pre-crisis period.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the CDS–stock connection concentrated on sovereign CDSs, a few studies have examined the relationship between CDS spreads and the stock market at the country level ([ 4 , 20 , 21 , 22 , 23 , 24 ]). Estimating a vector autoregressive generalized conditional heteroskedastic VAR-BEKK(Baba, Engle, Kraft and Kroner) model, with the purpose of explaining the dependency structures between credit spreads and equity returns of the European market (based on iTraxx Europe index, the Dow Jones Euro Stoxx 50 index and the Dow Jones VStoxx index), Schreiber et al [ 20 ] found that the negative relationship between asset prices and credit spreads is valid only for the pre-crisis period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical literature that dealt with the CDS–stock market connections has applied multivariate time series models, including the Vector Autoregressive (VAR) model ([ 5 , 13 , 20 , 21 ]), the Vector Error Correction Model ([ 4 , 17 ]), the Granger causality tests ([ 6 , 24 ]), Autoregressive Distributed Lag approach ([ 14 ]) and, recently, new econometric tools such as Markov regime-switching models ([ 15 ]), quantile-on-quantile methodology and the nonparametric causality-in-quantiles tests ([ 11 ]) and transfer entropy ([ 12 ]). The concept of entropy is used to depict nonlinear dependence within the financial returns series [ 25 ].…”
Section: Literature Reviewmentioning
confidence: 99%